A Bibliometric Analysis of Trends, Research Focus, and Research Development on E-Modules as Learning Media in Education - Agustin, Dian Ayu; Pamungkas , Heni Purwa; Dewi, Retno Mustika (Equilibrium: Jurnal Pendidikan, 2026)
This study aims to analyze publication trends, research focus, and the development of e-module research as learning media in the field of education through a bibliometric approach. Data were obtained from the Scopus database, with a total of 83 open-access English-language articles from the period 2015–2024 analyzed using Biblioshiny. The analysis results indicate that publication trends have experienced a significant increase, particularly during the period 2022–2024. In terms of research focus, the conceptual structure is dominated by the themes of e-learning, education, and human interaction, which reflects the role of e-modules as learning media in the context of educational technology. Meanwhile, the topics of e-modules, critical thinking, and problem-based learning were identified as emerging themes, indicating that e-module research is still in a strengthening phase and has not yet fully become mainstream in research. From the developmental perspective, the study shows an increase in global research contributions involving various countries, with dominant contributions coming from Indonesia. Overall, the findings of this study affirm that research on e-modules as learning media is in a developmental phase with great potential for further investigation, particularly in strengthening the position of e-modules as learning media in technology-based educational research.